Dynamic 3D Imaging DAGM 2009 Workshop, Dyn3D 2009, Jena, Germany, September 9, 2009, Proceedings - Kolb, Andreas; Koch, Reinhard (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2009)
3D imaging sensors have been investigated for several decades. Recently, - provements on classical approaches such as stereo vision and structured light on the one hand, and novel time-of-?ight (ToF) techniques on the other hand have emerged, leading to 3D vision systems with radically improvedcharacter- tics. Presently, these techniques make full-range 3D data available at interactive frame rates, and thus open the path toward a much broader application of 3D vision systems. The workshop on Dynamic 3D Vision (Dyn3D) was held in conjunction with the annual conference of the German Association of Pattern Recognition (DAGM) in Jena on September 9, 2009. Previous workshops in this series have focused on the same topic, i.e., the Dynamic 3D Vision workshopin conjunction with the DAGM conference in 2007 and the CVPR workshop Time of Flight Camera-Based Computer Vision (TOF-CV) in 2008. The goal of this year's workshop, as for the prior events, was to constitute a platform for researchers working in the ?eld of real-time range imaging, where all aspects, from sensor evaluation to application scenarios, are addressed. After a very competitive and high-quality reviewing process, 13 papers were accepted for publication in this LNCS issue. The research area on dynamic 3D vision proved to be extremely lively. Again, as for prior workshops on this ?eld, numerous new insights and novel approaches on time-of-?ight sensors, on re- time mono- and multidimensional data processing and on various applications are presented in these workshop proceedings.